2015
DOI: 10.1111/sms.12627
|View full text |Cite
|
Sign up to set email alerts
|

How 100‐m event analyses improve our understanding of world‐class men's and women's sprint performance

Abstract: This study aimed to compare the force (F)-velocity (v)-power (P)-time (t) relationships of female and male world-class sprinters. A total of 100 distance-time curves (50 women and 50 men) were computed from international 100-m finals, to determine the acceleration and deceleration phases of each race: (a) mechanical variables describing the velocity, force, and power output; and (b) F-P-v relationships and associated maximal power output, theoretical force and velocity produced by each athlete (P , F , and V )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
131
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(152 citation statements)
references
References 47 publications
17
131
0
4
Order By: Relevance
“…A previous study reported that sprinting performance was improved by submaximal (60-70% of the maximal speed in the 100-m sprint) sprint training with BFR [11]. Based on the relationship between average and maximal running speeds in the 100-m race (e.g., 10 m/s on average and 11.2 m/s at the maximum) [14], 75-85% of the average speed of their best record of the 100-m race can be considered as 67-76% of the maximal speed. While the range of running speeds in our study was slightly higher than that in the previous study [11], the participants (sprinters) in this study comfortably performed submaximal sprinting at 75-85% of the average speed of their best record of the 100-m race rather than the lower speed range based on the pilot test.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study reported that sprinting performance was improved by submaximal (60-70% of the maximal speed in the 100-m sprint) sprint training with BFR [11]. Based on the relationship between average and maximal running speeds in the 100-m race (e.g., 10 m/s on average and 11.2 m/s at the maximum) [14], 75-85% of the average speed of their best record of the 100-m race can be considered as 67-76% of the maximal speed. While the range of running speeds in our study was slightly higher than that in the previous study [11], the participants (sprinters) in this study comfortably performed submaximal sprinting at 75-85% of the average speed of their best record of the 100-m race rather than the lower speed range based on the pilot test.…”
Section: Methodsmentioning
confidence: 99%
“…When the duration of the race is longer than 3mn, the maximal valueσ ofV O2 is reached, σ is a decreasing function of time at the end of the race or an increasing linear function of energy, and therefore (22) implies that v is increasing again.…”
Section: Bounding Variations Of the Forcementioning
confidence: 99%
“…Here, we use the data of [10] to produce the velocity curve andV O2 curve in Figure 6. Again, we can derive information from (22): when in the part whereV O2 is linearly increasing, on the singular arc we have (17) with α > 0 and the velocity is decreasing; on the part where σ is constant, the velocity is constant, and when σ is linearly decreasing, we have (17) with α < 0 and the velocity is increasing so that there is a final sprint. The very last points where the velocity decreases again are due to the zero energy part at the end of the optimization.…”
Section: Bounding Variations Of the Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Para que un atleta sea capaz de mantener la máxima velocidad hasta el final de la carrera, unos altos niveles de producción de fuerza y potencia son necesarios si se quiere vencer a la fatiga y las alteraciones neuronales (Slawinski et al, 2017). Pese a ello se ha expuesto en la literatura científica un descenso de variables como la fuerza horizontal media (Girard, Brocherie, Tomazin, Farooq y Morin, 2016;Slawinski et al, 2017) o la potencia media (Slawinski et al, 2017 En Slawinski et al (2017) las fuerzas horizontales medias y la potencia media en la fase de deceleración fueron significativamente mayores en los hombres que en las mujeres (p≤ 0.001), tanto en Newtons (N) como en porcentaje respecto al peso corporal (%BW).…”
Section: ! 49unclassified